Study of the Radio-Protective Effects of Henna Mixed With Vinegar on the Skin of Irradiated Rats - Mojgan Hasanzade; Mohammad Taghi Bahreyni Toossi; Masoumeh Gharib; Shirin Taraz Jamshidi; Hamid Gholamhosseinian; Shokouhozaman Soleymanifard (Iranian Journal of Medical Physics)
Introduction: Skin damage is one of the most common challenges of radiation therapy. In the present study an attempt was made to evaluate the radio-protective effects of henna mixed with vinegar on the skin.Material and Methods: The rats were divided into Control (no treatment), R (receiving radiation alone), V (receiving vinegar alone), H (receiving henna mixed with vinegar), R + H (receiving henna mixed with vinegar and then radiation), and R + V (receiving vinegar and then radiation) groups. All rats were euthanized and their skins’ pathological damage and the level of super oxide dismutase (SOD) and Mallon dialdehyde (MDA) were evaluated. The rats were irradiated with 15 Gy (6MV) X-rays.Results: Increase MDA and decrease SOD were seen in R group. However, these changes were ameliorated in R + H group, although the difference was not significant. Vinegar significantly decreased MDA induced by radiation, but could not increase the SOD level. The rate of skin pathological damage in R group were higher than in Control. However, the level of these lesions was lower in R + H and R + V groups compared to R group. The rate of dermatitis and sweat gland atrophy in R + H and R + V groups were less than R group and similar to the level in the control group.Conclusion: Henna and vinegar could reduce the skin injuries induced by radiation. Regarding pathological injuries, the effects of vinegar alone was more than henna, but regarding antioxidant activity, the protective effect of henna mixed with vinegar was better than vinegar alone.